Supporting mental wellbeing of UK health and care workers using a mobile application: a mixed-methods feasibility study - Yildirim, Mehmet (2024)
Background Poor mental wellbeing is highly prevalent among health and care workers, causing decreased individual health and patients’ safety as well as leading to organisational problems. Prioritising mental wellbeing support for this population is crucial for promoting a healthy work environment. Mobile application-based self-care interventions have emerged as promising tools in recent decades due to their ease of implementation, cost-effectiveness, and user-friendliness. While numerous studies have demonstrated their effectiveness in promoting mental wellbeing, the scoping review revealed limited research focused specifically on health and care workers. Furthermore, existing interventions often target specific aspects of mental wellbeing, such as stress, burnout, anxiety, and depression, neglecting the broader mental wellbeing concept. Additionally, the literature identified a lack of qualitative studies exploring the experiences of health and care workers using these interventions. To address these gaps, this study employed a mobile application-based self-monitoring tool encompassing various aspects of mental wellbeing, from physical components to mental health conditions. The study also incorporated qualitative individual interviews to gain deeper insights into the participants' experiences with mental wellbeing monitoring via a mobile application.